Karakteristik Kecelakaan Lalu Lintas dan Pendidikan Keselamatan Berlalulintas Sejak Usia Dini: Studi Kasus di Kabupaten Purbalingga - Gito Sugiyanto; Mina Yumei Santi (Semesta Teknika, 2015)
Traffic accidents increased along with the increase in road traffic violations. One of the victims of traffic accidents is children. Road safety awareness and culture of children can be improved by doing the traffic safety education from an early age and promotion of the importance of road safety for children. Pedestrian is one of the vulnerable road users. The aim of this study is to investigate the characteristics of traffic accident in Purbalingga District, Central Java Province and the characteristics of the vehicle speed on arterial roads without median and introduces the principle of crossing the road by using 4-T procedure that is (Tunggu sejenak, Tengok kanan, Tengok kiri, dan Tengok kanan lagi) or waiting for a moment, look right, look left, and look right again to children from an early age. Based on the analysisof an accident data from 2010 till 2013, motorcycles are vehicles most involved accident followed by truck.Characteristics of speed in arterial roads without median with the function as a school district obtained a mean of the speed is 56.80 km/h. The probability of a pedestrian who was hit motorcycle or car passengers with this speed (56.80 km/h) will die is 90%.